1997
DOI: 10.1097/00007632-199707010-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bone Quality on Pedicle Screw Loading in Axial Instability

Abstract: Although small changes in pedicle morphometry can alter screw bending moments significantly, changes in cancellous modulus had no measurable impact on bending moments at these same loads. Bone density is likely to play a limited role in screw bending failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 41 publications
0
31
0
2
Order By: Relevance
“…According to the previous studies, the injection of PMMA along the entire length of the screw results in the highest pullout strength [14]. The pedicle area provides approximately 60% of the pullout strength [6], which means the more zones (especially the pedicle area) that involve PMMA, the stronger the pull-out strength of the pedicle screw.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to the previous studies, the injection of PMMA along the entire length of the screw results in the highest pullout strength [14]. The pedicle area provides approximately 60% of the pullout strength [6], which means the more zones (especially the pedicle area) that involve PMMA, the stronger the pull-out strength of the pedicle screw.…”
Section: Discussionmentioning
confidence: 93%
“…In some patients, surgical treatment is unavoidable. An osteoporotic spine presents a significant challenge for a spinal surgeon to manage [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…These have been rightly classified as bony failure and not implant failure. Osteoporosis is one factor which should always be accounted in the preoperative planning [3,4]. As surgeons, we have the options of using sublaminar wires (unpublished data), hooks [5], or cement augmented screws [6,7] in severely osteoporotic cases.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] Most bony failure studies have focused on the influence of BMD. [17][18][19][20] However, no studies have reported on the change in the trabecular bone loading during screw placement or following pedicle screw removal. Routine implant removal following general fracture healing is still somewhat controversial due to the perceived risks and benefits.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] Most bony failure studies have focused on the influence of bone mineral density (BMD). [17][18][19][20] The specific aim of the current study is to investigate the trabecular strain behavior following pedicle screw placement. The authors hypothesized that the trabecular strain adjacent to the screw would be significantly greater than the strain of the same bone before screw placement.…”
Section: Introductionmentioning
confidence: 99%